Individual credit market experience and beliefs about bank lending policy: Evidence from a firm survey - Jarko Fidrmuc; Christa Hainz; Werner Hölzl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
We study how firms' individual credit market experience influences their beliefs about the bank lending policy, using the Austrian Business Survey between 2011 and 2016. Firms which have recently experienced a loan rejection are more likely to believe that the lending policy is restrictive. We see similar effects for firms who were granted loans, but with conditions worse than anticipated. Exploiting the panel structure shows that firms without recent credit market experience are less likely to change their beliefs, which converge towards the middle category. Our findings are in line with theories of rational inattention and with asymmetric experience effects.
Keywords: G21; E51; D22; 330; Formation of beliefs; rational inattention; pessimism; persistence; behavioral macroeconomics